Glue Embolization of the Giant Aneurysm by Reducing Thrombosis-Induced Volume Expansion Effect - Yoo Kyung Yeom (대한영상의학회지, 2015)
A giant aneurysm due to a large intra-aneurysmal volume can be complicated by a delayed massive volume expansion caused by thrombus formation. To prevent such a severe mass effect, we obliterated the aneurysmal lumen by gluing and prevented further development of thrombosis. A 52-year-old female with a giant aneurysm at the cavernous segment of the internal carotid artery presented with tinnitus and intermittent diplopia. After confirming with a negative occlusion test, the right internal carotid artery was trapped by coiling and with further obliteration of the aneurysmal lumen by gluing. She developed a mild diplopia after the procedure and recovered without any deficit. The magnetic resonance angiography showed a stable occlusion of the aneurysm and good collateral filling of the cerebral vessel 15 months later.